2011
DOI: 10.1055/s-0031-1300281
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Antioxidant Activity of the SH Metabolite I of Erdosteine on Human Neutrophil Oxidative Bursts

Abstract: Acute and chronic lung diseases both lead to an extensive recruitment of neutrophils in the lungs. These cells play a major defensive role but, when activated, they are also an important source of reactive oxygen species, which generate a cytotoxic oxidant stress that triggers a self-sustaining phlogogenic loop. Erdosteine (CAS 84611-23-4) is a mucoactive drug whose metabolization leads to active metabolites with an SH group, and molecules bearing an SH group are also considered to have antioxidant activity. L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
33
0
4

Year Published

2011
2011
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 21 publications
4
33
0
4
Order By: Relevance
“…The minimal active concentration of Met I was 2.5 g/ml for Tempol, Fremy's salt and HO ؒ radicals. These findings are not only of the same order of magnitude as the biological findings previously obtained when Met I was used to investigate the release of ROS and RNS from human neutrophil bursts [14,15] , but also extend its range of activity as the minimal concentration of Met I still active on neutrophil bursts is 5 g/ml.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The minimal active concentration of Met I was 2.5 g/ml for Tempol, Fremy's salt and HO ؒ radicals. These findings are not only of the same order of magnitude as the biological findings previously obtained when Met I was used to investigate the release of ROS and RNS from human neutrophil bursts [14,15] , but also extend its range of activity as the minimal concentration of Met I still active on neutrophil bursts is 5 g/ml.…”
Section: Discussionsupporting
confidence: 81%
“…Glutathione is emerging as one of the most important antioxidant defence mechanisms in oxidant-induced lung injury and inflammation [7] : its lung and nose concentrations are 140 and 40 times that found in plasma [8][9][10][11] , and provide an important indication about the natural defensive strategy adopted by the airways to defend themselves. On the basis of this observation, various low-weight soluble molecules bearing an SH group, such as N-acetylcysteine, mesna, thiopronine and dithiothreitol or the prodrugs stepronin and erdosteine, have been used for therapeutic purposes [7,[12][13][14] .…”
Section: Introductionmentioning
confidence: 99%
“…It is a mucolytic agent which contains two blocked sulfhydryl groups that are released following its metabolic process. It has been shown that its active metabolites have exhibited free radical scavenging and anti-inflammatory activities [3,9]. In this study, the improved renal function in the pigs treated with erdosteine resulted in the stimulation of antioxidation activities by CAT, and GPx.…”
mentioning
confidence: 62%
“…The title Erdosteine (S-1-[(carboxymethyl)sulfanyl]-N-(2-oxotetrahydro-3-thienyl)acetamide) was first disclosed in FRP 2, 502,153 and USP 4,411,909 [1,2]. It was introduced as a mucolytic agent for chronicp ulmonary diseases more than 15 years ago.…”
Section: Discussionmentioning
confidence: 99%